(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2024)
The manufacturing sector in Nigeria, which includes industries such as food and beverages, textiles, chemicals, and automotive, faces significant challenges due to outdated infrastructure, limited access to advanced technologies, and a shortage of skilled labour. Foreign Direct Investment (FDI) plays a crucial role in improving sector performance, highlighting the need for strategic interventions. While some firms still use traditional methods, others explore smart manufacturing technologies. Early adopters of smart manufacturing demonstrate potential benefits and obstacles, such as inadequate infrastructure, high costs, limited access to advanced technologies, economic barriers, skills gaps, brain drain, inadequate government support, and regulatory hurdles. To address these issues, the paper recommends developing infrastructure, forming partnerships with tech firms, providing government subsidies and grants, encouraging private investment, and enhancing workforce development through training and collaboration with educational institutions. Policy recommendations include creating supportive regulations and establishing industry standards to promote smart manufacturing. The paper also examines successful implementations of smart factories in other countries and suggests initiating pilot projects in Nigeria to demonstrate feasibility and benefits. Adopting smart manufacturing technologies is forecasted to positively impact Nigeria’s economy by increasing productivity, efficiency, and competitiveness in the manufacturing sector.